2t-24=-27+5t

Simple and best practice solution for 2t-24=-27+5t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t-24=-27+5t equation:


Simplifying
2t + -24 = -27 + 5t

Reorder the terms:
-24 + 2t = -27 + 5t

Solving
-24 + 2t = -27 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
-24 + 2t + -5t = -27 + 5t + -5t

Combine like terms: 2t + -5t = -3t
-24 + -3t = -27 + 5t + -5t

Combine like terms: 5t + -5t = 0
-24 + -3t = -27 + 0
-24 + -3t = -27

Add '24' to each side of the equation.
-24 + 24 + -3t = -27 + 24

Combine like terms: -24 + 24 = 0
0 + -3t = -27 + 24
-3t = -27 + 24

Combine like terms: -27 + 24 = -3
-3t = -3

Divide each side by '-3'.
t = 1

Simplifying
t = 1

See similar equations:

| 4s-27=-31+6s | | 7.50x=750 | | h=-16t^2+75t+8 | | 5y=1000 | | 6*1r=36 | | y=3sin(x) | | 2(3+2x)-1=17 | | 5y-(8-y)=2[-4-(3+5y)-13] | | 3(b+2)=4b-10 | | 10+3[x+2]=31 | | -5x+6=3x-9 | | log(12x+2)=log(2x-1)+1 | | 16xy+x^2+64y^2=0 | | 4+1f=17 | | 4k-12-6k=2k-6+6k+2 | | ln(2-1)=0 | | 4k-12-6=2k-6+6k+2 | | x^3-4x^2+6x=0 | | 8-3d=12 | | 432=-16t^2+64t+512 | | 2x^5-3x^4-2x^3+7x^2-2x-6=0 | | c^2-16h^4=0 | | 6r+3-2t+4=5 | | cosh(x)*cos(x)=1 | | 90=60+t | | -3b+23=80 | | 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= |

Equations solver categories